2020
DOI: 10.1159/000510793
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Inflammatory Features of Exacerbation-Prone Asthma: A Cross-Sectional Study Using Multidimensional Assessment

Abstract: <b><i>Background:</i></b> Reducing asthma exacerbations is a major target of current clinical guidelines, but identifying features of exacerbation-prone asthma (EPA) using multidimensional assessment (MDA) is lacking. <b><i>Objective:</i></b> To systemically explore the clinical and inflammatory features of adults with EPA in a Chinese population. <b><i>Methods:</i></b> We designed a cross-sectional study using the Severe Asthma Web-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The rate of BD responsiveness shows a direct dose-response relationship with long-term mortality in patients with asthma [ 25 ]. Moreover, bronchial responsiveness is a risk factor for exacerbation-prone asthma in a Chinese cohort [ 26 ]. In this regard, our findings show that administering only salbutamol does not identify all treatment-naïve patients with BDR, and patients showing reversibility to ipratropium could be undetected and misclassified as non-reversible.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of BD responsiveness shows a direct dose-response relationship with long-term mortality in patients with asthma [ 25 ]. Moreover, bronchial responsiveness is a risk factor for exacerbation-prone asthma in a Chinese cohort [ 26 ]. In this regard, our findings show that administering only salbutamol does not identify all treatment-naïve patients with BDR, and patients showing reversibility to ipratropium could be undetected and misclassified as non-reversible.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, guidelines for the clinical management of asthma patients with moderate or severe symptoms continue to overlook the effect of individual patient characteristics as potential contributors or determinants of future risk. In fact, previous investigations have shown that inflammatory mediators, including eosinophilia and increased airflow limitation, are associated with a higher risk of exacerbation in severe and refractory asthma 26–28 . However, none of these studies attempted to assess, in a parametric manner, how inflammatory markers and phenotypical characteristics correlate with symptom control (ACQ‐5) and other clinical and demographic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous investigations have shown that inflammatory mediators, including eosinophilia and increased airflow limitation, are associated with a higher risk of exacerbation in severe and refractory asthma. [26][27][28] However, none of these studies attempted to assess, in a parametric manner, how inflammatory markers and phenotypical characteristics correlate with symptom control (ACQ-5) and other clinical and demographic characteristics. F I G U R E 6 Heat map showing the probability of at least one exacerbation within the first year of treatment for patients receiving monotherapy or combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein to study of the asthma exacerbation‐prone phenotype, work has been done to study CRS patients who have frequent AECRS or an exacerbation‐prone phenotype 27 . We have previously proposed that AECRS‐prone be defined as having at least 4 AECRS episodes in a 12 months period 18 based on previous guidelines indicating that at least 1 rescue medication in 3 months was an indication of uncontrolled CRS 1 .…”
Section: Epidemiologymentioning
confidence: 99%
“…26 In a similar vein to study of the asthma exacerbation-prone phenotype, work has been done to study CRS patients who have frequent AECRS or an exacerbation-prone phenotype. 27 We have previously proposed that AECRS-prone be defined as having at least 4 AECRS episodes in a 12 months period 18 based on previous guidelines indicating that at least 1 rescue medication in 3 months was an indication of uncontrolled CRS. 1 In a retrospective review of over 3000 patients with CRS, 19.3% were found to have meet this criteria for exacerbation-prone CRS, with at least 4 AECRS (defined by an antibiotic course prescribed for worsening sinus symptoms) over a 12 months period.…”
Section: Epidemiologymentioning
confidence: 99%